Correction: Engineering an adhesive based on photosensitive polymer hydrogels and silver nanoparticles for wound healing. Issue 6 (31st January 2022) - Tang, Qinqing; Chen, Canwen; Jiang, Yungang; Huang, Jinjian; Liu, Ye; Nthumba, Peter M.; Gu, Guosheng; Wu, Xiuwen; Zhao, Yun; Ren, Jianan
Abstract : Correction for 'Engineering an adhesive based on photosensitive polymer hydrogels and silver nanoparticles for wound healing' by Qinqing Tang et al., J. Mater. Chem. B, 2020, 8, 5756–5764, DOI: ; 10.1039/d0tb00726a .